Chitosan and Cystatin/Lysozyme Preparation as Protective Edible Films Components. (28th October 2015) - Zimoch-Korzycka, Anna; Rouilly, Antoine; Bobak, Łukasz; Jarmoluk, Andrzej; Korzycki, Michał
Abstract : This work characterizes biological, physical, and chemical properties of films formed from an aqueous solution of hydroxypropyl methylcellulose (HPMC), with different concentrations of chitosan (CH) and bioactive cystatin/lysozyme preparation (C/L). The properties of biocomposites were examined by Dynamic Mechanical Analysis (DMA), Fourier's transfer infrared spectroscopy (FTIR), water vapour permeability (WVP), and tensile testing. Antimicrobial activity against Micrococcus flavus, Bacillus cereus, Escherichia coli, Pseudomonas fluorescens, and Candida famata was conducted. Films glass transition and storage modulus were dependent on the C/L and CH concentration. Modulus values decreased during the temperature scan and with higher reagents levels. An increase of CH and C/L concentrations in the films resulted in a decrease in tensile strength from 2.62 to 1.08 MPa. It suggests the hydrolyzing influence of C/L, also observed in smaller peak size of α relaxation. C/L addition caused shiftingT g to higher temperature. DMA and FTIR analysis proved that HPMC and CH are compatible polymers. Water resistance was improved with rising CH concentration from1.08 E - 09 to7 . 71 E − 10   g / m ∗ s ∗ P a . The highest inhibition zone in M. flavus and C. famata was recorded at the highest concentration of CH and C/L.